2018
DOI: 10.2478/avutgs-2018-0004
|View full text |Cite
|
Sign up to set email alerts
|

Investiganting Correlation LST and Vegetation Indices Using Landsat Images for the Warmest Month: A Case Study of Iasi County

Abstract: In this paper is investigating correlation between land surface temperature and vegetation indices (Normalized Difference Vegetation Index - NDVI, Enhanced Vegetation Index 2 - EVI2 and Modified Soil Adjusted Vegetation Index - MSAVI) using Landsat images for august, the warmest month, for study area. Iaşi county is considered as study area in this research. Study Area is geographically situated on latitude 46°48'N to 47°35'N and longitude 26°29'E to 28°07'E. Land surface temperature (LST) can be used to defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…After quality inspection and cloud masking several images were discarded, resulting in a dataset of 125 Landsat-5 images and 60 Landsat-8 images (Level-1 for the thermal bands and Level-2 for multispectral bands). These images covered two time periods, (a To estimate the land surface temperature from the Landsat thermal infrared bands, the method that was described in [17] was followed. The method requires the estimation of the NDVI using the red and near-infrared bands of the multispectral images.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After quality inspection and cloud masking several images were discarded, resulting in a dataset of 125 Landsat-5 images and 60 Landsat-8 images (Level-1 for the thermal bands and Level-2 for multispectral bands). These images covered two time periods, (a To estimate the land surface temperature from the Landsat thermal infrared bands, the method that was described in [17] was followed. The method requires the estimation of the NDVI using the red and near-infrared bands of the multispectral images.…”
Section: Methodsmentioning
confidence: 99%
“…This has as a consequential warming effect in northeastern Europe [16]. Related work also exists on the evaluation of the relationship between different vegetation indices and LST [15,17], pointing out the negative correlation between LST and NDVI.…”
Section: Introductionmentioning
confidence: 99%
“…It means, each ecosystem has its own set of variable atmospheric conditions. Importantly, because a high LST corresponds to a low NDVI and vice versa, the negative correlation between LST-NDVI is relevant for urban climate research and other fields of science (Carlson et al, 1994;Anbazhagan et al, 2016, Macarof et al, 2018. The Vis other than the NDVI that have a negative correlation with LST can also be employed for climaterelated research.…”
Section: Relationship Between Lst and The Vis In Dry And Rainy Seasonsmentioning
confidence: 99%
“…Some of these studies can be found in Deng et al (2018), Guechi et al (2021), and Koko et al (2021). Furthermore, Macarof et al (2018) investigated the correlation between LST and NDVI, MSAVI, and EVI only in the warmth season. Similarly, Alademomi et al (2020) assessed the association of LST, NDVI and EVI with land cover changes in dry season.…”
Section: Introductionmentioning
confidence: 99%